Islamic Crowdfunding Model for Accelerating Asset Growth in Sharia Cooperatives: A Case Study of KSBB - Diah Krisnaningsih; Ninda Ardiani; Tofan Tri Nugroho; Dyah Ayu Nur Aini; Dian Maharani Saputri (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study analyzes the implementation of sharia loan crowdfunding at Koperasi Syariah Berkah Bersama (KSBB) as an innovative financing model to accelerate asset growth and the accumulation of third-party funds (DPK) in non-bank financial institutions. Using a qualitative case study approach, data were collected through in-depth interviews with KSBB management, members, and beneficiaries (shahibul maal and mudharib), supported by observations of the KSBB Universe platform and relevant documentation. The findings reveal that the adoption of sharia crowdfunding significantly increased KSBB’s assets from IDR 513 million in 2020 to IDR 6.9 billion in 2023 (growth of 1,350%) through the use of WhatsApp-based crowdfunding, and further to IDR 13.8 billion in March 2024 (growth of 150%) after the introduction of the KSBB Universe platform. Key success factors include KSBB’s hybrid role as a consumer cooperative, sharia financing provider, and crowdfunding operator; the application of syariah contracts (murabahah, mudharabah, musyarakah); strict project feasibility analysis; strong community trust and religious values; and the adoption of a digital platform that enhances transparency and accessibility. However, challenges remain in terms of members’ financial literacy, limited regulatory frameworks for cooperative-based crowdfunding, and the need for stronger human resource capacity. The study contributes theoretically by extending the discourse on sharia crowdfunding beyond fintech startups into cooperative-based models, and practically by offering insights into how cooperatives can adapt crowdfunding mechanisms to strengthen financial sustainability and promote sharia-based financial inclusion in Indonesia.